Legitimacy of Taiwan’s Trade Negotiations with China: Demystifying Political Challenges - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2016)
The article analyzes Taiwan’s legitimacy debate over trade negotiations with China. The theoretical concept of legitimacy is used to assess Taiwan’s cross-straits negotiation mechanism and trade agreements. This article argues that Taiwan’s current legal framework governing congressional supervision of cross-straits agreements falls short of procedural legitimacy and performance legitimacy. By explaining the constitutional design for Taiwan’s “white glove” mechanism, the article explores the initial procedural legitimacy deficit. As cross-straits negotiations involve increasingly substantive obligations, the legitimacy of bilateral agreements has changed fundamentally. The massive protest in the Sunflower Movement due to the Services Trade Agreement reinforced legitimacy concerns. Taiwan’s ambiguous congressional review procedures and negative public perception undermine performance legitimacy of cross-straits agreements. Notwithstanding the conclusion of free trade agreements (FTA) with Singapore and New Zealand, Taiwan’s domestic political impasse will jeopardize its efforts to integrate into regional FTAs. Hence, the legitimacy of Taiwan’s law and politics regarding cross-straits negotiations will have a profound impact on its cross-straits and foreign trade policies.